Health Screening: Blood Glucose, Blood Pressure, and Body Composition Examination in RT 005 RW IV, Kelurahan Gondoriyo, Ngaliyan, Semarang - Qisthi Fariyani; Irman Said Prastyo; Heni Sumarti; Sheilla Rully Anggita; Moch Husain; Delia Okta Rahmadani1; Munawarohthus sholikha (Community Research and Application Journal (CRAJ), 2026)
Non-communicable diseases (NCDs) such as diabetes mellitus, hypertension, and obesity remain a major public health burden in Indonesia. National data (Riskesdas, 2018) reported a hypertension prevalence of 34.1% among Indonesian adults and a diabetes mellitus prevalence of 10.9% among the population aged 15 years and above, with many cases undetected because these conditions are often asymptomatic in their early stages. This community health screening was carried out on Sunday, 14 June 2026, at Beringin Forest Park, Kelurahan Gondoriyo, Kecamatan Ngaliyan, Semarang, as part of the community service program of the Department of Physics, Universitas Islam Negeri Walisongo Semarang. The activity provided free examination of blood glucose (capillary method), blood pressure (digital tensimeter), and body composition (bioelectrical impedance analysis), together with education on the procedures and individual consultation for participants with abnormal findings. Of 16 participants screened for blood glucose, 81.3% (13 participants) fell within the normal range, while one participant (6.3%) recorded a value in the diabetes range requiring immediate medical evaluation. Of 17 participants screened for blood pressure, only 23.5% (4 participants) had normal blood pressure, whereas 70.6% (12 participants) fell into the Hypertension Stage 1 or Stage 2 category. Mean body fat percentage exceeded normal reference ranges for both female (34.3%, n = 11) and male (24.3%, n = 4) participants. These findings indicate a considerable burden of undetected cardiometabolic risk factors within this community and demonstrate the value of low-cost, university–community screening partnerships for early detection and referral. Given the limitations of single-visit measurement, confirmatory examination by authorized medical personnel is recommended for participants with abnormal results.